Family Law and French Law in Vanuatu: An Opportunity Missed? - Farran, Sue (Victoria University of Wellington Law Review, 2004)
This article outlines the need for the courts in Vanuatu to adopt a more robust approach in developing a relevant regional jurisprudence by considering certain aspects of French family law which remain potentially applicable under the Constitution of Vanuatu as law existing at independence. With reference to selected areas of family law, it explains how a more vigorous comparative approach using French law may be useful for filling gaps which presently exist in national legislation and also illustrates how certain dimensions of French family law may be particularly suited to the contemporary Vanuatu context.